2022
DOI: 10.1038/s41419-022-05233-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-myogenic mesenchymal cells contribute to muscle degeneration in facioscapulohumeral muscular dystrophy patients

Abstract: Muscle-resident non-myogenic mesenchymal cells play key roles that drive successful tissue regeneration within the skeletal muscle stem cell niche. These cells have recently emerged as remarkable therapeutic targets for neuromuscular disorders, although to date they have been poorly investigated in facioscapulohumeral muscular dystrophy (FSHD). In this study, we characterised the non-myogenic mesenchymal stromal cell population in FSHD patients’ muscles with signs of disease activity, identified by muscle magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…This indicates that the DUX4–HIF1α axis is not as simple as expected and that targeting HIF1α might be challenging in the context of FSHD therapeutic approaches. Finally, given (I) the regeneration defects in FSHD [ 89 , 90 , 91 ], (II) the role of HIF1α in this process [ 38 , 40 ] and (III) the impact of DUX4 expression on the HIF1α pathway depending on the differentiation state, further investigations, especially in cellular actors of muscle regeneration (e.g., satellite cells) appear critical for a better understanding of FSHD-associated muscle regeneration disturbances. Moreover, regarding the pivotal role of HIF1α in muscle metabolism, it will be important to clarify whether metabolic disturbances could contribute to the development of muscle dysfunction in FSHD.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the DUX4–HIF1α axis is not as simple as expected and that targeting HIF1α might be challenging in the context of FSHD therapeutic approaches. Finally, given (I) the regeneration defects in FSHD [ 89 , 90 , 91 ], (II) the role of HIF1α in this process [ 38 , 40 ] and (III) the impact of DUX4 expression on the HIF1α pathway depending on the differentiation state, further investigations, especially in cellular actors of muscle regeneration (e.g., satellite cells) appear critical for a better understanding of FSHD-associated muscle regeneration disturbances. Moreover, regarding the pivotal role of HIF1α in muscle metabolism, it will be important to clarify whether metabolic disturbances could contribute to the development of muscle dysfunction in FSHD.…”
Section: Discussionmentioning
confidence: 99%
“…FAPs are activated and proliferate after muscle injury and differentiate following specific molecular cues into specialized cells that prepare the extra-cellular matrix to support muscle regeneration. Mis-regulation of FAP function has been implicated in aberrant muscle regeneration in several neuromuscular disorders including LGMD2B [ 85 ], ALS [ 86 ] and recently FSHD [ 53 , 55 , 58 ]. FAP dysregulation in FSHD was first noted in a mouse model of stochastic transient DUX4 expression, which resulted in an increased FAP gene expression signature [ 58 ] that was validated histologically and found to associate with muscle fibrosis post injury [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Myogenic cells are not the only perturbed cell type in FSHD, implicating non-myogenic cell types resident in muscle, particularly fibroadipogenic progenitor (FAP) cells [ 53 , 58 ]. FAPs comprise a heterogenous mesenchymal cell population, which interact with immune cells and muscle stem cells to facilitate muscle regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that the DUX4-HIF1α axis was not as simple as expected and that targeting HIF1α might be challenging in the context of FSHD therapeutic approaches. Finally, given (I) the regeneration defects in FSHD [79,80], (II) the role of HIF1α in this process [41], (III) the impact of DUX4 expression on the HIF1α pathway depending on the differentiation state, further investigations, especially in satellite cells, appear critical for a better understanding of FSHD-associated muscle regeneration disturbances. Moreover, regarding the pivotal role of HIF1α in muscle metabolism, it will be important to clarify whether metabolic disturbances could contribute to the development of muscle dysfunction in FSHD.…”
Section: Targeted Hif1α Knock Down In Mice Exacerbates Dux4-induced M...mentioning
confidence: 99%